Chemical weathering and erosion responses to changing monsoon climate in the Late Miocene of Southwest Asia. (13th June 2019) - Clift, Peter D; Kulhanek, Denise K; Zhou, Peng; Bowen, Melanie G; Vincent, Sophie M; Lyle, Mitchell; Hahn, Annette
Abstract: The late Miocene is a time of strong environmental change in SW Asia. Himalayan foreland stable isotope data show a shift in the dominant vegetation of the flood plains away from trees and shrubs towards more C4 grasslands at a time when oceanic upwelling increased along the Oman margin. We present integrated geochemical and colour spectral records from International Ocean Discovery Program Site U1456 in the eastern Arabian Sea to reconstruct changing chemical weathering and erosion, as well as relative humidity during this climatic transition. Increasing hematite/goethite ratios derived from spectral data are consistent with long-term drying after c . 7.7 Ma. Times of dry conditions are largely associated with weaker chemical alteration measured by K/Rb and reduced coarse clastic flux, constrained by Si/Al and Zr/Al. A temporary phase of increased humidity from 6.3 to 5.95 Ma shows a reversal to stronger weathering and erosion. Wetter conditions can result in both more and less alteration due to the nonlinear relationship between weathering rates, precipitation and sediment transport times. Trends in relative aridity do not follow existing palaeoceanographic records and are not apparently linked to changes in Tibetan or Himalayan elevation, but more closely correlate with global cooling. An apparent opposing trend in the humidity evolution in the Indus compared to southern China, as tracked by spectrally estimated hematite/goethite, likely reflects differences in the topography in the Indus compared to the Pearl River drainage basins, as well as the generally wetter climate in southern China.